Updated distribution of Zoropsis spinimana (Dufour, 1820; Araneae: Zoropsidae) in Germany and novel insights into its ecology based on a citizen science survey - Wirth, Alexander; Schulemann-Maier, Gaby (Frontiers in Arachnid Science, 2024)
In Germany, Zoropsis spinimana (Dufour, 1820) is an introduced, likely synanthropic spider species. Here, we report the results of a nationwide mapping appeal conducted by the citizen science platform NABU-naturgucker.de, used to assemble live distributional data for the species in Germany. With the help of media interest in this species, we gathered a valuable dataset and a large image gallery of the species. In just five weeks, we received more than 15,000 records, representing a 2.3-fold increase in occupied territory compared to previous knowledge. By analyzing the data in detail, we obtained novel insights into the ecology and eco-geography of Z. spinimana in Germany, including information on prey, coloration, potential predators, altitudinal distribution and temporal appearance, along with two cases of accidental human translocation.